Saint training - Fixmer, Elizabeth, 1952- (Grand Rapids, Mich. : Zonderkidz, 2010)
During the turbulent 1960s, sixth-grader Mary Clare makes a deal with God: she will try to become a saint if He provides for her large, cash-strapped family.
Keywords: Catholics -- Fiction; Christian life -- Fiction; Conduct of life -- Fiction; Family problems -- Fiction; Schools -- Fiction; Nineteen sixties -- Fiction